Development and biomaterial characterization of Mg-Li-Zn-Ca alloys. (December 2022) - Okafor, Chiamaka; Datye, Amit; Zhang, Shuhan; Schwarz, Udo D.; Cai, Yong; Munroe, Norman
Abstract: Alloy design is a fundamental approach to developing Mg-based bioresorbable implant materials that possess the desired mechanical and degradation behavior required for treatment. Mg-Zn-Ca alloys have received significant interest as bioresorbable implant materials because of superior mechanical properties and lower degradation rates. However, they are prone to localized corrosion which jeopardizes their mechanical strength and causes premature implant failure. In this study, lithium has been added to Mg-1Zn-0.5Ca to promote uniform degradation and room temperature ductility. Alloys with Li content up to 4 wt% exhibited a hcp structure, with ∼12 % elongation and evidence of pitting. Alloys with 8 wt% Li had a duplex structure, with ∼30 % elongation and no evidence of pitting. Alloys with 11 wt% exhibited a single-phase bcc structure, with ∼33 % elongation and a lithium carbonate surface coating. The 8 and 11 wt% Li alloys had a reduced metal dissolution, which resulted in a high viability of HUVEC cells, making them attractive for biodegradable stent materials. The improvement in mechanical and degradation properties of these Mg-Li-Zn-Ca alloys were achieved through a reduction of secondary phases, formation of a lithium carbonate surface coating and phase transformation from a hexagonal close packed to a duplex and body centered cubic structures. Additionally, the relatively higher hardness, and elastic moduli of these alloys are desirable to prevent stent recoil after deployment. Graphical Abstract: ga1 Highlights: At least 67 % reduction in grain size was achieved for all alloys with Li addition. Ductility tripled as Li content increased from 4 to 8 wt% with a slight increase in strength. Mg alloys with 8 wt% and 11 wt% Li exhibited no evidence of pitting. 90 % viability was achieved for HUVEC cells exposed to alloy degradation extracts.